PENERAPAN METODE PEMBELAJARAN TALKING STICK DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PKN KELAS VII-2 SMP NEGERI 3 KOTA TEBING TINGGI - Herlina Manurung (PGSD Universitas Negeri Medan, 2018)
This purposes of this research is to improve learning result on civics subject through talking stick method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VII-2 SMPNegeri 3Tebing Tinggi which amounted to 36 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the inquiry method of civics subjects can improve student learning result characterized by increased mastery learning students, namely cycle I (80,56%), cycle II (88,89 %) and complete learn the clasical equal to 88.23 %. Key words: Talking stick, Civic, Learning outcomes